TERT Promoter Mutations Are an Independent Predictor of Distant Metastasis in Middle Eastern Papillary Thyroid Microcarcinoma - Parvathareddy, Sandeep Kumar; Siraj, Abdul K.; Iqbal, Kaleem; Qadri, Zeeshan; Ahmed, Saeeda O.; Al-Rasheed, Maha; AlQatie, Ahmed A.; Al-Sobhi, Saif S.; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Endocrinology, 2022)
Background: Papillary thyroid microcarcinomas (PTMCs) have been attributed to the recent increased incidence of thyroid cancer. Although indolent, a subset of PTMC could potentially develop distant metastasis (DM). This study aimed to evaluate the clinico-pathological features and molecular characteristics of PTMC and identify the risk factors for DM in PTMC patients from Middle Eastern ethnicity. Methods: We retrospectively analyzed 210 patients with histologically confirmed PTMC. Clinico-pathological associations for DM, BRAF mutation and TERT mutation were analyzed successfully in 184 patients. Multivariate analysis was performed using Cox proportional hazards model and logistic regression analysis. Results: Among the PTMC patients included in this cohort, DM was noted in 6.0%(11/184), whereas tumor relapse occurred in 29/184 (15.8%). Of the 11 cases with DM, lung metastasis occurred in 8 cases, bone metastasis in 2 cases and brain metastasis in 1 case. Presence of extrathyroidal extension and older age were significantly associated with DM. Molecular analysis showed BRAF V600E mutations to be the most frequent, being detected in 45.7% (84/184). TERT promoter mutations were detected in 16 (8.7%) cases and were significantly associated with DM and shorter metastasis-free survival in multivariate analysis. Conclusions: Our study indicates a surprisingly high frequency of TERT promoter mutation in Saudi patients with PTMC. Identifying TERT promoter mutations as an independent predictor of DM in patients with microcarcinoma could explain the inherent aggressive nature of PTMC from Middle Eastern ethnicity and magnify its role in patient risk stratification, which might help in improving therapeutic strategy for these patients.